Strand 4: Information Technology and Social Exclusion - Clarke, Alan (Proceedings of the International Conference on Networked Learning, 1998)
For individuals to play a full part in the expanding information society requires them to have the skills and knowledge to use information and communication technologies (ICT). However, a large part of the adult population although aware of ICT do not perceive it as beneficial to themselves. How can the initial experience of ICT be provided to adults so that they are willing to take part and have an effective experience? A key factor in aiding attendance is the location. Adults will attend a familar location if it is acceptable to them, nearby and the events are scheduled to meet their needs. A wide range of approaches including outreach, taster sessions, drop-in facilities and conventional courses can be effective in improving their confidence and overcoming their initial anxiety. Adults are motivated to attend events for several reasons but one critical factor relates to their children. The desire to help their children or simply to keep up with them is a major reason in their desire to attend. However, the fear of being left behind by the world is also important as is simple curiosity. Basic courses are often heavily influenced in their design by funding restrictions and this may result in learners’ experience being limited co a particular course of study no matter what their needs are.